Cultural Heritage on line Empowering users: an active role for user communities Florence, 15th - 16th December 2009 - Cirinnà, Chiara; Lunghi, Maurizio (Proceedings e report, 2010)
The 2nd International Conference "Cultural Heritage online - Empowering users: an active role for user communities" was held in Florence on 15-16 December 2009. It was organised by the Fondazione Rinascimento Digitale, the Italian Ministry for Cultural Heritage and Activities and the Library of Congress, through the National Digital Information Infrastructure and Preservation Program - NDIIP partners. The conference topics were related to digital libraries, digital preservation and the changing paradigms, focussing on user needs and expectations, analysing how to involve users and the cultural heritage community in creating and sharing digital resources. The sessions investigated also new organisational issues and roles, and cultural and economic limits from an international perspective.